Improving Listening Skills Using Learning Video Media for Fifth Grade Students of SD Negeri 118 Bengkulu Utara - Lathifah Lamis; Eli Rustinar; Hasmi Suyuthi (Universitas Cokroaminoto Palopo, 2025)
From the results of initial observations made by the author at State Elementary School 118 Bengkulu Utara, researchers found that there was a lack of utilization of learning media and there were still many students who were less active during the learning process. This study aims to determine how the results of improving the student learning process using learning video media on short films to improve listening skills of fifth grade students of SD Negeri 118 North Bengkulu. This research uses quantitative methods with experimental research. The research subjects were grade V students totaling 22 students. Data collection techniques using One Group Pre Test - Post Test Design listening to the short film story